2020
DOI: 10.1161/circulationaha.120.047164
|View full text |Cite
|
Sign up to set email alerts
|

The Variety of Cardiovascular Presentations of COVID-19

Abstract: Information about a real patient is presented in stages (boldface type) to expert clinicians (Drs Uriel and Sayer), who respond to the information and share their reasoning with the reader (regular type). A discussion by the authors follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
509
2
41

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 516 publications
(558 citation statements)
references
References 5 publications
6
509
2
41
Order By: Relevance
“…In addition, some of these patients may have a "STEMI-mimicker" such as focal myocarditis or stress cardiomyopathy known to be associated with COVID-19 13,14 . Fibrinolysis of these patients would provide no benefit to the patient, but still incur bleeding risk and eventual invasive diagnostic catheterization given that the ST-elevation is unlikely to resolve.…”
Section: ) Patients Presenting With Stemi To a Primary Pci Center A)mentioning
confidence: 99%
“…In addition, some of these patients may have a "STEMI-mimicker" such as focal myocarditis or stress cardiomyopathy known to be associated with COVID-19 13,14 . Fibrinolysis of these patients would provide no benefit to the patient, but still incur bleeding risk and eventual invasive diagnostic catheterization given that the ST-elevation is unlikely to resolve.…”
Section: ) Patients Presenting With Stemi To a Primary Pci Center A)mentioning
confidence: 99%
“…Interestingly, a combination of inhibitors of both proteases blocked the virus entry in vivo effectively [22]. Given the vast representation of the receptors as mentioned above in human tissues, the virus itself has a broad capacity to infect various human cell types and induce different pathogenic chains of events that correspond with a variety of clinical pictures of COVID-19 [14,24,25]. Viral replication begins in the ciliated epithelium of the nasal cavity with the highest expression of its receptors in the goblet/secretory cells and the highest virus yield found in nasal swabs [18,24].…”
Section: The Sars-cov-2 Virus Its Transmission and Entry Pointsmentioning
confidence: 99%
“…Elevated cardiac biomarkers have been identified in COVID-19 patients, especially in those with severe conditions. Of note, recent case reports highlighted cardiac involvement as a complication associated with COVID-19, even without respiratory symptoms [30,52]. Myocardial injury, defined as elevated cardiac biomarkers, was found in five of the first 41 patients (12%) with COVID-19 in Wuhan, which mainly manifested as an increase in high-sensitivity cardiac troponin I (hs-cTnI) levels (>28 pg/mL) [8].…”
Section: Myocardial Injurymentioning
confidence: 99%
“…Moreover, the first description of critically ill patients from the United States indicated that 33% of the ICU patients developed cardiomyopathy [50]. Most recently, Fried et al described three cases of COVID-19 infection with acute systolic heart failure [30], suggesting that isolated myocarditis, myocarditis secondary to cytokine storm, stress-cardiomyopathy, and hypoxemia on underlying cardiovascular disease could be considered as potential mechanisms of left ventricular dysfunction. However, given the scarce availability of data regarding this topic, it remains unclear whether the acute heart failure following COVID-19 is mainly due to exacerbation of pre-existing cardiac dysfunction or new-onset cardiomyopathy.…”
Section: Decompensated Heart Failure and Mixed Shockmentioning
confidence: 99%
See 1 more Smart Citation